2022
DOI: 10.21203/rs.3.rs-2143584/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thermophilic Dehalococcoidia with unusual traits shed light on an unexpected past

Abstract: The phylum Chloroflexota is ubiquitous; however, its biology and evolution are poorly understood due to limited cultivability. Here, we isolated two motile, thermophilic bacteria from hot spring sediments belonging to the class Dehalococcoidia within the phylum Chloroflexota. A combination of cryo-electron tomography, exometabolomics, and cultivation experiments using stable isotopes of carbon revealed three unusual traits: flagellar motility; a peptidoglycan-containing cell envelope; and heterotrophic activit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…The phylum Chloroflexota constitutes a highly diverse and deeply branching lineage of bacteria. Currently, it is categorized into nine classes (Kochetkova et al, 2020;Yan et al, 2020;Palmer et al, 2023): Anaerolineae, Ardenticatenia, Caldilineae, Chloroflexia, Dehalococcoidia, Ktedonobacteria, Thermoflexia, Thermomicrobia, and a class-level SAR202 cluster of uncultured bacteria. Members of the Anaerolineaceae family exhibit a broad distribution in anaerobic environments, including marine sediments, deep hot aquifers, soils, and anaerobic digesters.…”
Section: Discussionmentioning
confidence: 99%
“…The phylum Chloroflexota constitutes a highly diverse and deeply branching lineage of bacteria. Currently, it is categorized into nine classes (Kochetkova et al, 2020;Yan et al, 2020;Palmer et al, 2023): Anaerolineae, Ardenticatenia, Caldilineae, Chloroflexia, Dehalococcoidia, Ktedonobacteria, Thermoflexia, Thermomicrobia, and a class-level SAR202 cluster of uncultured bacteria. Members of the Anaerolineaceae family exhibit a broad distribution in anaerobic environments, including marine sediments, deep hot aquifers, soils, and anaerobic digesters.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we describe the identification and subsequent characterization of one such BVMO from Chloroflexota bacterium strain G233 dubbed ssnBVMO. 25 Following the identification of ssnBVMO, we sought to address another major hurdle for the large-scale implementation of BVMOs: the requirement for stoichiometric quantities of the expensive NADPH cofactor. Previous work has overcome this issue by fusing BVMOs to coenzyme regenerating enzymes (CREs).…”
Section: Methodsmentioning
confidence: 99%
“…Since this organism grows optimally at a temperature of 75 °C, we tentatively identified the protein encoded by A0A2A9HFE7 as a thermostable BVMO that we dubbed ssnBVMO. 25,30 S5). [31][32][33] The presence of these motifs within the sequence of ssnBVMO strongly suggested that the identified enzyme would catalyze Baeyer-Villiger oxidations.…”
Section: Using Sequence Similarity Network To Identify a Thermostable...mentioning
confidence: 99%
“…To infer the evolutionary events that gave rise to the current distribution of genes associated with nitrogen metabolism and pH homeostasis, consensus presence/absence KO count pro les for the species with high-quality genomes available were generated from the EggNOG functional annotations as described before (75). From here, a cladogram inferred from the species tree (Fig.…”
Section: Ancestral Character State Reconstructionmentioning
confidence: 99%